Exploring cyanobacteria from the Andaman mangroves of Thailand Descriptions of new species of Desertifilum, Roseofilum, Tigrinifilum, and Persinema using a polyphasic approach - Ginn, Billy Lim Chun (Journal of phycology, 2025)
© 2025 Phycological Society of America.